Direction of trade : annual 1960-73 - World Bank.; International Monetary Fund. Bureau of Statistics (Washington, D.C. : International Monetary Fund, 1963)
"This publication provides ... seven years of data about 150 countries and two sets of world and area summaries ..."--Verso of cover, 1971-77.
Vols. for 1959/63 and 1965/69 not published.
Vols. for 1958/62-1970/74 issued with the International Bank for Reconstruction and Development.
Keywords: Commercial statistics -- Periodicals